Outpatient intraperitoneal catumaxomab therapy for malignant ascites related to advanced gynecologic neoplasms - Kurbacher, Christian M.; Hildenbrand, Ralf (The oncologist, 2015)
Background: Catumaxomab (CATU) is a trifunctional antibody approved for intraperitoneal (i.p.) treatment of malignant ascites (MA) related to carcinomas expressing the epithelial cell-adhesion molecule (EpCAM). CATU is mostly given to hospitalized patients, although outpatient treatment seems appropriate in selected individuals. This observational trial sought to obtain more detailed information regarding the feasibility of CATU in outpatients with MA related to various gynecologic tumors, including epithelial ovarian (EOC) and metastatic breast cancer (MBC). Materials and Methods: A total of 30 patients were included, 17 with EOC, 7 with MBC, and 6 with other malignancies. The patients had failed a median of 5 (range 1-12) previous systemic treatments. CATU was administered via an indwelling i.p. catheter at four increasing doses (i.e., 10, 20, 50, and 150 µg) given at 4-day intervals over 2 weeks. Toxicities were scored according to the Common Terminology Criteria for Adverse Events, version 4.03. Puncture-free survival (PuFS) was calculated from the start of CATU until the next puncture for MA, death, or loss to follow-up. Overall survival (OS) was calculated from the start of CATU to death from any reason or loss to follow-up. We also investigated various clinical parameters to predict PuFS and OS. These included age, tumor type, performance status, intensity of pretreatment, presence of extraperitoneal metastases, relative lymphocyte count at baseline, patient adherence to therapy, and the patients’ ability to undergo systemic treatment after CATU. Results: CATU was exclusively given on an outpatient basis, and 19 patients (63.3%) received all four planned i.p. instillations. Toxicity was the reason for discontinuation in only 2 patients. Toxicity was generally manageable, with abdominal pain, nausea/vomiting, fatigue, and fever the predominant adverse effects. Secondary hospitalization was necessary for 7 patients (23.3%), with a general deteriorated condition in 5 and fever/infection or abdominal pain in 1 patient each. Subsequent systemic treatment was possible in 11 patients (36.7%). Only 5 patients (16.7%) required a second puncture after i.p. CATU. The median PuFS was 56 days, and the median OS was 79.5 days. Positive predictors of both PuFS and OS were performance status, absence of extraperitoneal tumor, the capability to receive all four CATU infusions, and the ability to undergo subsequent systemic treatment. Conclusion: Outpatient i.p. CATU therapy for MA related to various gynecologic carcinomas is safe and effective in producing good ascites control in most individuals, allowing for subsequent systemic therapy in a substantial proportion of patients. Implications for Practice: Intraperitoneal treatment with the trifunctional antibody catumaxomab (CATU) was possible in a selected population of 30 outpatients with malignant ascites due to epithelial female genital tract or breast carcinoma. Toxicity was largely manageable. Patients in good condition at baseline, without extraperitoneal tumor and/or liver metastases, and with the ability to complete all four planned CATU instillations and the capability of undergoing subsequent systemic therapy benefited the most in terms of both puncture-free and overall survival. Outpatient i.p. CATU is safe and effective in a selected group of patients with malignant ascites due to various gynecologic malignancies and could be cost-saving compared with an inpatient approach.